Modeling of a New Structure of Precision Air Conditioning System Using Secondary Condenser for Rh Regulation - Subiantoro, Aries; Nasruddin, Nasruddin; Yusivar, Feri; Al-Hamid, Muhammad Idrus; Budiardjo, Bagio (UI Scholars Hub, 2012)
A dynamic mathematical model for a new structure of precision air conditioning (PAC) has been developed. The proposed PAC uses an additional secondary condenser for relative humidity regulation compared to a basic refrigeration system. The work mechanism for this system and a vapour-compression cycle process of the system are illustrated using psychrometric chart and pressure-enthalpy diagram. A non-linear system model is derived based on the conservation of mass and energy balance principles and then linearized at steady state operating point for developing a 8th-order state space model suited for multivariable controller design. The quality of linearized model is analyzed in terms of transient response, controllability, observability, and interaction between input-output variables. The developed model is verified through simulation showing its ability for imitating the nonlinear behavior and the interaction of input-output variables.